Quantum Dots: Quantum Optical Signature of Plasmonically Coupled Nanocrystal Quantum Dots (Small 38/2015). Issue 38 (October 2015) - Wang, Feng; Karan, Niladri S.; Nguyen, Hue Minh; Mangum, Benjamin D.; Ghosh, Yagnaseni; Sheehan, Chris J.; Hollingsworth, Jennifer A.; Htoon, Han
<x xml:space="preserve">Abstract</x> Artificial atoms, such as quantum dots, usually emit independently when they are separated by more than 10 nm. H. Htoon and co‐workers show on page 5028 that the strongly enhanced electromagnetic field of a pair of gold nano‐antenna (i.e., a plasmonic field) can induce coupling among quantum dots, causing them to emit as a single quantum emitter. The coupled quantum dots can be considered a 'quantum dot molecule', with potential application as the fundamental units of quantum‐controlled devices for switching and routing single photons that carry bits of quantum information.